2020
DOI: 10.1055/s-0039-3400313
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Assessment of Block Recession Trochleoplasty and Partial Parasagittal Patellectomy in Cats

Abstract: Objective The aim of this study was to assess computed tomography (CT) images of cadaveric feline stifles and record the relationship between the patella and femoral trochlea in normal stifles; then to investigate the effect of block recession trochleoplasty (BRT) with and without partial parasagittal patellectomy (PPP) on patellofemoral contact, depth of patellar recession and size of trochlea and patella. Materials and Methods The sample population included six cat cadavers (12 stifles). Preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 13 publications
4
22
1
Order By: Relevance
“…However, more recent publications have suggested additional techniques are required, such as a partial patellectomy, based on the unique anatomy in the cat. [4][5][6] A weak correlation with hip dysplasia and patellar luxation in cats has also been described. 3 Skeletal deformities have been reported in dogs with patellar luxation with a malalignment of the quadriceps mechanism leading to a medially directed force on the patella and consequently medial luxation.…”
Section: Introductionmentioning
confidence: 94%
“…However, more recent publications have suggested additional techniques are required, such as a partial patellectomy, based on the unique anatomy in the cat. [4][5][6] A weak correlation with hip dysplasia and patellar luxation in cats has also been described. 3 Skeletal deformities have been reported in dogs with patellar luxation with a malalignment of the quadriceps mechanism leading to a medially directed force on the patella and consequently medial luxation.…”
Section: Introductionmentioning
confidence: 94%
“…Partial parasagittal patellectomy was necessary in all four surgeries described in this case series in order to establish patellar tracking in contact with the recessed sulcus and to stabilize the patella. This technique has been previously reported clinically, 24 and was shown to improve the depth of patellar recession over that achieved with block recession trochleoplasty alone in a cadaveric study using CT. 55 The feline patella is relatively wider than the feline femoral trochlear sulcus, 56 and ex vivo studies in cats have shown that following block recession trochleoplasty alone, the feline trochlea becomes too narrow to accommodate it. 55 Instead, the patella rides the trochlear ridges and loses contact with the trochlear sulcus.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been previously reported clinically, 24 and was shown to improve the depth of patellar recession over that achieved with block recession trochleoplasty alone in a cadaveric study using CT. 55 The feline patella is relatively wider than the feline femoral trochlear sulcus, 56 and ex vivo studies in cats have shown that following block recession trochleoplasty alone, the feline trochlea becomes too narrow to accommodate it. 55 Instead, the patella rides the trochlear ridges and loses contact with the trochlear sulcus. The clinical impact of partial parasagittal patellectomy long term has not been reported; however, no intra- or postoperative complications related to this procedure were encountered in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Patella width exceeded the width of the sulcular part of the trochlear prosthesis and, as such, accurate patella-to-trochlear prosthesis fitting was deemed to be suboptimal; the patella rode on trochlear ridges rather than being in contact with prosthesis sulcus. Partial parasagittal patellectomy was performed 9 which, subjectively, improved patella fit and contact within the prosthetic trochlea.…”
Section: Case Reportmentioning
confidence: 99%
“…7 Techniques reported for the correction of MPL include femoral trochlear sulcoplasty, tibial tuberosity transposition, lateral retinacular imbrication, medial soft tissue release 1 distal femoral corrective osteotomy, 8 and partial parasagittal patellectomy. 9 Patellar groove replacement (PGR) has been reported in the literature as a surgical technique for the treatment of canine patellar luxation associated with severe femoro-patellar osteoarthritis. 10 To the authors' knowledge, this is the first case of PGR in a cat in published literature.…”
Section: Introductionmentioning
confidence: 99%